Pengaruh Model Discovery Learning berbantuan Peer Scaffold terhadap Scientific Reasoning Skills Siswa SMP dalam Pembelajaran IPA - Zakiyah Izza Avkarinah (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect of the discovery learning model assisted by peer scaffolding on junior high school students’ scientific reasoning skills in science learning. The research employed a quantitative approach with a quasi-experimental design in the form of a pretest–posttest control group design. The research subjects were seventh-grade students divided into an experimental class and a control class. The experimental class received instruction using the discovery learning model assisted by peer scaffolding, while the control class was taught using conventional learning methods. The research instrument consisted of a scientific reasoning skills test administered before and after the treatment. The data were analyzed using statistical tests appropriate to the characteristics of the data. The results showed that there was a difference in the improvement of scientific reasoning skills between students who learned through the discovery learning model assisted by peer scaffolding and those who learned through conventional instruction.
FINALISASI oleh Agus 2026 Juni 10
Keywords: Discovery Learning; Peer Scaffolding; Scientific reasoning Skills; Science Learning; Junior High School Students